“They don’t have a name for what he is”: The strategic de-characterization of Hannibal Lecter - Cámara-Arenas, Enrique (International Journal of English Studies, 2019)
This essay challenges the myth of Hannibal Lecter, in Demme’s The Silence of the Lambs, as an enigmatic and unclassifiable character. Lecter’s enigma is generated through a largely unexplored process of de-characterization, i.e. by recurrently presenting him through the speech of other characters who describe him as unknowable. After considering Lecter’s case against the background of well-known literary unknowabilities, a deductive phenomenological exploration of Lecter’s de-characterization is carried out with the assistance of tools from the disciplines of personality and social psychology, and supported by empirical evidence from those fields. The demystifying of Lecter’s unreadability does not entail a debasement of the film or the character. On the contrary, Lecter’s de-characterization, albeit a form of narrative manipulation, is viewed as responsible for much of the film’s impact and success. It produces sensitivity-boosting effects; it mediates the indirect characterization of the other characters; and it engages the spectators’ self-image thus contributing importantly to the enjoyment and appreciation of the film.